Nanostructured Lipid Carriers Improve Skin Permeation and Chemical Stability of Idebenone - Li, Bei (Springer US, 2012)
Idebenone (IDB) is a synthetic antioxidant and analog of coenzyme Q10. The percutaneous permeation of IDB was investigated in guinea pig skin after application of different formulations. The enhancing effects of various formulations [nanostructured lipid carriers (NLCs), nanoemulsion (NE), or oil solution] on the permeation of IDB were evaluated using ex vivo guinea pig skins. Furthermore, stability of different formulations and in which chemical stability of IDB was determined during storage. Permeation experiments revealed that formulations varied in their ability to enhance the skin permeation of IDB. For NLC formulation, the cumulative amount of IDB in the epidermis, dermis, and acceptor medium of diffusion cells was approximately threefold more than NE or oil solution at the end of 24-h experiment. No significant difference between NE and oil solution was observed in the enhancement of penetration efficacy of IDB. Different formulations resulted in stability with different properties. NLC formulation revealed preferentially more stable than NE. The residual percentage of IDB loaded in NLCs, NE, and oil solution was 90.1%, 65.4%, and 51.3%, respectively, when stored at 40°C under 75% RH and 3,000 lx light conditions for 180 days. The results obtained here demonstrated that the abilities of NLCs to improve the chemical stability of IDB and enhance the skin permeation are much better than NE and oil solution. These suggest that NLCs containing IDB have significant potential use for skin care as an alternative topical formulation.